Glutathione peroxidase‐1 overexpressing transgenic mice are protected from neurotoxicity induced by microcystin‐leucine‐arginine. Issue 10 (4th August 2018) - Shin, Eun‐Joo; Hwang, Yeong Gwang; Pham, Duc Toan; Lee, Ji Won; Lee, Yu Jeung; Pyo, Dongjin; Jeong, Ji Hoon; Lei, Xin Gen; Kim, Hyoung‐Chun
Abstract: Although it has been well‐recognized that microcystin‐leucine‐arginine (MCLR), the most common form of microcystins, induces neurotoxicity, little is currently known about the underlying mechanism for this neurotoxicity. Here, we found that MCLR (10 ng/μL/mouse, i.c.v.) induces significant neuronal loss in the hippocampus of mice. MCLR‐induced neurotoxicity was accompanied by oxidative stress, as shown by a significant increase in the level of 4‐hydroxynonenal, protein carbonyl, and reactive oxygen species (ROS). Superoxide dismutase‐1 (SOD‐1) activity was significantly increased, but glutathione peroxidase (GPx) level was significantly decreased following MCLR insult. In addition, MCLR significantly inhibited GSH/GSSG ratio, and significantly induced NFκB DNA binding activity. Because reduced activity of GPx appeared to be critical for the imbalance between activities of SODs and GPx, we utilized GPx‐1 overexpressing transgenic mice to ascertain the role of GPx‐1 in this neurotoxicity. Genetic overexpression of GPx‐1 or NFκB inhibitor pyrrolidine dithiocarbamate (PDTC) significantly attenuated MCLR‐induced hippocampal neuronal loss in mice. However, PDTC did not exert any additive effect on neuroprotection mediated by GPx‐1 overexpression, indicating that NFκB is a neurotoxic target of MCLR. Combined, these results suggest that MCLR‐induced neurotoxicity requires oxidative stress associated with failure in compensatory induction of GPx, possibly through activation of the transcription factor NFκB.